50.8k views
3 votes
PLESE HELPPP!!!!!!!!!!!!!!!!

PLESE HELPPP!!!!!!!!!!!!!!!!-example-1
User Nilda
by
4.6k points

1 Answer

1 vote

Answer:

B.
(6)/(2x^(2) - 5x)

Explanation:

The product of the ratioal expressions given above can be found as follows:


= (2)/(x) * (3)/(2x - 5)

Multiply the denominators together, and the numerators together, separately to get a single expression


(2(3))/(x(2x - 5))


= (6)/(x(2x) - x(5))


= (6)/(2x^(2) - 5x)

The product of the expression
\ = (2)/(x)*(3)/(2x - 5) =
(6)/(2x^(2) - 5x)

The answer is B.